The Effect of the World Exchange Indexes (DJIA, SSEC and NIKKEI 225) on the Indonesia Stock Exchange Index (IDX) - Lesmana, Alvin (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
This study aims to determine the effect of the Dow Jones Industrial Average (DJIA), Shanghai Stock Exchange Composite (SSEC) and Nikkei 225 Indexes on the movement of the Indonesian Stock Exchange Index (IDX) for the period of November 2016 – November 2021. This study uses non-participant observation methods and the whole population in that time period is used as a sample. Data analysis techniques include descriptive statistics, classical assumption test. The results of the multiple linear regression analysis showed that the DJIA and Nikkei 225 indexes partially had a positive effect on the IDX, while the SSEC Index had no effect on the IDX. However, the value of (R2) shows that only 16.6 percent of the IDX movement can be partially explained by research variables, while 83.4 percent is influenced by factors outside this study.